Experiences of Discrimination Reported by Turkish, Moroccan and Bangladeshi Muslims in Three European Cities - Bruss, Joachim (Journal of ethnic and migration studies, 2008)
This investigation explores discrimination against Muslims in three European cities. Experiences and perceptions of discrimination are related to the histories of immigration in European countries, political arrangements for Muslims in Europe, participation in the structure and culture of receiving societies, and-especially since the attacks on 11 September 2001 in the US-perceptions of Muslims in European cities. Considering the efforts of the Committee on the Elimination of Racial Discrimination (CERD) and the International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) to be a top-down method, the complementary approach taken in this paper is to examine the victim's perspective via a bottom-up method and to study the perceptions of those who suffer discrimination. The sample for my study consists of Turkish Muslims from Berlin (n=225), Bangladeshi Muslims from London (n=135) and Moroccan Muslims from Madrid (n=203) who were interviewed between July and December 2004. Turkish and Moroccan Muslims often said that they belong to a minority that is discriminated against; Bangladeshi Muslims regarded themselves as much less often discriminated against, though significant numbers of younger Bangladeshi Muslims perceived themselves as subject to discrimination. In addition, I examine factors that lead to an increase in perceived discrimination. Results from multiple logistic regression analysis indicate that everyday experiences-such as being stopped by the police, verbal attacks, or disrespectful treatment in public-particularly increase the likelihood of one claiming to belong to a minority that is discriminated against.